Cushioning energy absorption of composite layered structures including paper corrugation, paper honeycomb and expandable polyethylene. (April 2019) - Guo, Yanfeng; Ji, Meijuan; Fu, Yungang; Pan, Dan; Wang, Xingning; Kang, Jianfen
The composite layered structures including paper corrugation, paper honeycomb and expandable polyethylene are innovative structures of cushioning energy absorption, and the compression and impact resistances of the expandable polyethylene can be enhanced by laminating the corrugated paperboard or honeycomb paperboard. This article evaluated the compression performance and cushioning energy absorption of the composite layered structures by the static compression and drop impact compression tests. On one hand, the static compression properties showed that the total energy absorption, energy absorption per unit volume and stroke efficiency of the composite layered structures were all higher than those of expandable polyethylene. The specific energy absorption was enhanced with the increase in compression strain but almost not affected by the compression rate. The specific energy absorption of the composite layered structures including the expandable polyethylene and honeycomb paperboard was greater than those of the expandable polyethylene and corrugated paperboard. The energy absorption efficiency of the composite layered structures including the expandable polyethylene and corrugated paperboard was large for the low compression stress level, yet that of the composite layered structures including the expandable polyethylene and honeycomb paperboard was large for the high compression stress level. On the other hand, the dynamic compression characteristics showed that the peak stress, energy absorption per unit area, energy absorption per unit volume and specific energy absorption of the composite layered structures embodying paper sandwich cores and expandable polyethylene had linear increasing trends with the increase of drop shock energy. At the same drop impact condition, the composite layered structures including the honeycomb paperboard and expandable polyethylene had better cushioning energy absorption, the peak stress decreased by 23.6% on average, the energy absorption efficiency raised by 8.85% on average and the specific energy absorption increased by 18.1% on average than those including the corrugated paperboard and expandable polyethylene. Therefore, the corrugated paperboard and honeycomb paperboard can helpfully improve the cushioning energy absorption of the expandable polyethylene, and the composite layered structures embodying the expandable polyethylene, corrugated paperboard and honeycomb paperboard may hold excellent packaging protection.